Investigating Self-Assessment as a Platform of Student-Teacher’s Reflection in EFL Teaching Practice - Imelia Nurun Nafisah; Dea Silvani; Metty Agustine Primary; Dewi Rosmala (Siliwangi University, 2021)
This reflective practice study aims to investigate how self-assessment as a platform for self-reflection functions to promote student teacher’s professional development. This study involves the researcher herself as a student teacher who completed a teaching practice in a senior high school in Indonesia. To collect the necessary data, this study uses self-assessment, which consists of nine points of self-reflection, including (1) Organization, rules, and procedures; (2) Preparing students for new learning; (3) Positive relationship; (4) Deeping Learning; (5) Presenting new learning; (6) Helping students reflect on and celebrate learning; (7) Culture of thinking and learning; (8) Applying learning; (9) Engagement and Enjoyment. Then, the collected data are analyzed by using thematic analysis. The results showed that there are two main functions of self-assessment in a student teacher’s professional development, which are (1) to improve classroom management skill, and (2) to improve teaching strategy. To sum up, reflection by using self-assessment, which consists of nine assessed points related to the student teacher’s classroom teaching practices, can facilitate reflection on many things related to the teaching and learning process, which in turn can help the student teacher to improve her professional development.